Fingerprint Image Watermarking Using Encrypted Identification Number - Mustafa, Intan Shafinaz (2006)
Watermarking biometric data is growing importance and relatively new issue that used in authentication system. Watermarking is a technique of hiding specific data for copyright authentication. This data can be used to verify the ownership. Today, with the rapid growth of the Internet, the increased of functionality of computers and recent developments in fingerprint sensing technology for acquiring a fingerprint without using the traditional ink and paper make these image of biometric data (fingerprints) open to the potential attacks during transmission. Recipients required a mechanism which can prove the accuracy of their image. If the images are watermarked, it is easy for the owner to verify the images.